A phase I thorough QT/QTc study evaluating therapeutic and supratherapeutic doses of avacopan in healthy participants - Shichang Miao; Peter Staehr; Ezra Tai; Borje Darpo; Hongqi Xue; Danielle Armas; Kenneth Webster; Rajneet K. Oberoi (Wiley, 2024)
Abstract This phase I thorough QTc, double‐blind, randomized, placebo‐ and positive‐controlled, parallel group, multiple‐dose study evaluated avacopan's effect on cardiac repolarization using concentration‐QTc (C‐QTc) as the primary analysis. Avacopan 30 mg b.i.d. (therapeutic dose) was administered orally on days 1 through 7 followed by avacopan 100 mg b.i.d. (supratherapeutic dose) on days 8 through 14 in 29 healthy participants. Moxifloxacin 400 mg and placebo were administered on days 1 and 15 in a nested crossover design for assay sensitivity in separate cohorts to 28 participants. Time‐matched plasma concentrations and up to 10 replicate ECGs were obtained on prespecified days at baseline and postdose on days 1, 7, 14, and 15. The mean change from baseline on QTcF for avacopan (−5.5 to 3.5 ms) was similar to placebo (−6.9 to 1.4 ms) across days 1, 7, and 14. The mean effect on ΔΔQTcF (90% CI) was estimated as 1.5 ms (−0.17 to 3.09) and 0.8 ms (−2.41 to 4.05) for 30 and 100 mg avacopan b.i.d. treatments, respectively. Based on the C‐QTc analysis, avacopan's effect on ΔΔQTcF >10 ms can be excluded within the observed plasma concentration range of up to ~1220 and ~335 ng/mL for avacopan and active major metabolite, M1, respectively. The estimated population slopes showed a shallow relationship, which was not statistically significant. There was no clinically meaningful effect of avacopan on heart rate or cardiac conduction (PR and QRS intervals). Avacopan appeared to be generally well tolerated in this study population.